Faktor-Faktor yang Mempengaruhi Tingkat Pengangguran di Kota Banjarmasin Tahun 2009-2019 - Tina Sapuwati; Ika Chandriyanti (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
The purpose of this study was used to (1) analyze the effect of model 1 labor force participation rate, inflation, minimum wages and aconomic growth on unemployment; (2) to analyze the influence of model 2 the labor force, inflation, minimum wages and economic growth on unemployment; (3) to determine which factor is the most in influencing unemployment in Banjarmasin City.The source of the data used in this study is secodary data obtained through the Central Bureau of Statistic of the City of Banjarmasin and the Department of Cooperatives for Micro Enterprises and Manpower of Banjarmasin City. The analysis which will be stated through the F test (simultaneously) and T test (Partially) using the SPSS version 16.0 aplication.The results of this study indicate that (1) the level og labor force participation, inflation, minimum wages and economic growth individually (partially), inflation and economic growth have a significant effect on unemployment. While the labor force participation rate and the minimum wage do not have a significant effect on unemployment; (2) labor force, inflation, minimum wages and economic growth individual (partial), inflation and economic growth have a significant effect on unemployment. While the labor force and minimum wages have no significant effect on unemployment; (3) together (simultaneously) the level of labor force participation, inflation, minimum wages and economic growth have a positive and significant effect on unemployment; (4) together (simultaneously) the labor force, inflation, minimum wages, and economic growth have a positive and significant effect on unemployment; (5) the most dominant factor affecting unemployment in Banjarmasin City, model 1 is inflation, while model 2 is economic growth.